ANALISIS KEBIJAKAN HUKUM PIDANA DALAM PERLINDUNGAN SAKSI DENGAN KASUS PEMBERANTASAN KORUPSI - Tanjung, Andry Syafrizal (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
The problem today is that many law enforcement officers face difficulties in uncovering corruption cases which occur systematically. In some cases, it was reported that they did not report cases of corruption due to the threats, which were given to them, and the criminalization given to them. Corruption has become a massive societal phenomenon that is considered an extraordinary crime that threatens the Indonesian economy and hinders national development. All elements of society hope that it will not become an unresolved problem. As long as the legal policy in the effort to eradicate corruption is more than the perpetrators. The protection policy in corruption cases needs to be optimized because it can be an alternative legal instrument in eradicating corruption. This shows that the protection of witnesses and victims is an important and urgent legal aspect; because the legal policy in the corruption process is more on the perpetrators and pays less attention to legal investigations. It is necessary to optimize the role of LPSK in criminal law policies, including in providing protection for witnesses in corruption cases; Therefore, it is important to carry out legal reforms to the law on witness protection in the corruption process.